The Dilemma of Restorative Justice as Impunity for Perpetrators of Sexual Violence Against Children - Dewi Safira; Abdul Kholiq (Jurnal Daulat Hukum, 2025)
The increasing application of restorative justice in handling cases of child sexual violence in Indonesia has sparked controversy due to its potential to create impunity for perpetrators and neglect victims’ rights. This study aims to analyze the dilemma of restorative justice as a form of impunity in child sexual violence cases and to propose an ideal model that ensures the fulfillment of victims’ rights and the realization of substantive justice. The research employs a normative legal method using statutory and conceptual approaches. Primary and secondary legal materials are examined through qualitative analysis to identify inconsistencies between regulatory norms and practical implementation. The findings reveal that although restorative justice aims to restore victims and rehabilitate offenders, its misapplication especially when diversion is carried out without sufficient attention to the victim’s recovery may result in impunity and re-victimization. Furthermore, the lack of understanding among law enforcement officials, inadequate monitoring mechanisms, and social pressure contribute to ineffective victim protection. The study proposes a victim-centered restorative justice model that emphasizes comprehensive victim recovery, offender accountability, and active community participation supported by trained facilitators and strict supervision. The novelty of this research lies in offering a structured model for implementing restorative justice that balances victims’ and offenders’ rights, thereby ensuring substantive justice and preventing impunity in cases of child sexual violence.